Coded diagnoses from general practice electronic health records are a feasible and valid alternative to self-report to define diabetes cases in research. Issue 2 (April 2021) - de Boer, A.W.; Blom, J.W.; de Waal, M.W.M.; Rippe, R.C.A.; de Koning, E.J.P.; Jazet, I.M.; Rosendaal, F.R.; den Heijer, M.; Numans, M.E.; de Mutsert, R.
Highlights: Data extraction from general practice health records provided a follow-up rate of 97%. ICPC-coded diagnoses diabetes had an excellent agreement with the reference standard. ICPC-coded diagnoses DM were more accurate compared to self-reported DM. ICPC-coded diagnoses DM are feasible and valid for case definition in cohort studies. Abstract: Aims: To examine the feasibility and validity of obtaining International Classification of Primary Care (ICPC)-coded diagnoses of diabetes mellitus (DM) from general practice electronic health records for case definition in epidemiological studies, as alternatives to self-reported DM. Methods: The Netherlands Epidemiology of Obesity study is a population-based cohort study of 6671 persons aged 45–65 years at baseline, included between 2008−2012. Data from electronic health records were collected between 2012−2014. We defined a reference standard using diagnoses, prescriptions and consultation notes and investigated its agreement with ICPC-coded diagnoses of DM and self-reported DM. Results: After a median follow-up of 1.8 years, data from 6442 (97%) participants were collected. With the reference standard, 506 participants (79/1000 person-years) were classified with prevalent DM at baseline and 131 participants (11/1000 person-years) were classified with incident DM during follow-up. The agreement of prevalent DM between self-report and the reference standard was 98% (kappa 0.86), the agreement between ICPC-coded diagnoses and the reference standard was 99% (kappa 0.95). The agreement of incident DM between ICPC-coded diagnoses and the reference standard was >99% (kappa 0.92). Conclusions: ICPC-coded diagnoses of DM from general practice electronic health records are a feasible and valid alternative to self-reported diagnoses of DM.